Awareness of green practices influences current green activities by homestay operators in Kelantan - Chen, Yan Rong; Zainal, Nor Fatinah; Yaacob, Nor A’dilah; Alias, Muhamad Aidil Fitera (2015)
This study is to identify the awareness of green practice influences current green activities by home stay operators in Kelantan. Besides that, this study looked at awareness of home stay operator towards green activities in water management, energy efficiency and waste management. A total of 108 questionnaires were distributed to home stay operators in Kelantan and questionnaires were receive to use for data analysis. The data were analyzed using SPSS. Pearson correlation and descriptive statistic were used answered research objective. The pearson correlation used to measure the significance of linear bivariate between the independent variable thereby achieving the objective of this study. The descriptive statistic use to summarize and interpret some of the property of a set data which is sample but do not infer the properties of the population from which the sample was drawn by using the mean. This research was focus on the home stay in Kelantan that only registered from the Ministry of the Tourism and Culture Malaysia